Studi Kelayakan Bisnis Tour & Travel Pada PT. Indoloka Wisata Mandiri - Maya Carlina; Pandoyo (JURNAL ILMU ADMINISTRASI PUBLIK DAN BISNIS, 2020)
The background of this effort is the establishment of business development in the field of tourism is growing rapidly has become the need of the whole world. One of these efforts that we encounter is the travel business. In the middle of the work at this time and the noise of routines that occur in the metropolis, recreation or travel on the weekend with relatives an opportunity for travel agents for answering these problems. This study was conducted to determine the feasibility of a business tour & travel or travel agency in PT. Indoloka Wisata Mandiri from several aspects, namely: the market and marketing, technological, and financial aspects. This study is an exploratory feasibility study aimed to gain an overview and understanding of the problems and potential in business. Research shows that by using the marketing mix strategy (marketing mix) that must be carried out by PT. Indoloka Wisata Mandiri to increase the number of tourists to the attractions annually, by committing to the 7 strategies include Product Strategy, Pricing Strategy, Strategy place, HR Strategy, Promotion Strategy, Strategy Process, and Physical Evidence. Based on the financial aspects, with an initial investment of Rp 150,000,000, - with operational cash flow in 2015 amounted to Rp.129.300.000, -, 2016 Rp. 131 100 000, -, 2017 amounting to Rp 133 350 000, -, 2018 Rp. 135 150 000, -, Net Present Value (NPV) generated Rp. 268 140 450, - is a positive value, BCR results amounted to 2.787 or more than one (> 1), then it means a decent investment. Results ARR 63.15%> 10% DF as feasible, and the payback period is within 1 year, 2 months. That the market for a trip to the office or school student group has the potential market for a travel agency in Jakarta and surrounding areas and meet the eligibility criteria of the business.